Strategic Information Management -Challenges and Strategies in Managing Information Systems (Journal of Information Systems and Technology Management, 2004)
Robert D. Galliers and Dorothy E. Leidner Strategic Information Management -Challenges and Strategies in Managing Information Systems Butterworth-Heinemann, 2003, 3rd Edition, 625pp. ISBN: 0-7506-5619-0